A History of Architecture. Nineteenth Edition edited by John Musgrove - Fletcher, Sir Banister (1987)
Consultant Editors: John Tarn and Peter Willis. Assistant Editor: Jane Farron; 66-94: The Ancient near East: Early Mesopotamian Architecture. Assyrian A. Neo-Babylonian A. Early Anatolian and Hittite A. Urartian A. Phrygian A. Median and Persian A..